Student companion to Elie Wiesel - Sternlicht, Sanford V. (Student companions to classic writers., 2003)
Since it was written nearly 50 years ago, Night (1958) has changed world perception of the Holocaust experience. Wiesel's oeuvre, including Holocaust narratives such as Dawn (1961), novels, essays, tales, and plays, has also altered the critical and aesthetic landscape through which we view literature, placing themes of religious identity, hope, survival, devotion to family, and humanity ahead of distinctions of fiction and nonfiction. This volume offers critical analysis of all of Wiesel's major writings, with full chapters on Night, Dawn, The Oath, and four other full-length works. His most.